(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: Abortion is a spontaneous termination of pregnancy with various causes, including infections like cytomegalovirus (CMV). Cytomegalovirus is a common viral infection that can affect various organs and systems in the body. Aim of study: This research aims to investigate the concertation level of Cortisol and ACTH hormones that may play a role in crucial processes during pregnancy. Materials and methods: This study conducted at Maternity and Children’s Hospital in Hilla from November 2023 to March 2024 focused on 250 women who had undergone abortions. Participants were divided into two groups: 200 women with abortions (Positive Group) and 50 healthy married women (Control Group). Results: we found 60 Cytomegalovirus were positively obtained from women with abortion, The serological diagnosis for CMV-positive samples found that 6 samples were seropositive to CMV IgM, 14 samples were seropositive for both IgM & IgG, and 40 (samples were seropositive for CMV IgG only. The study investigated the concertation hormone levels of Cortisol and ACTH in women who had experienced abortions with cytomegalovirus (CMV) infection compared to a Control group of healthy married women. The results showed that the patient group had significantly lower cortisol levels, at a mean value of 42.1158. On the other hand,(ACTH) of (78.1468).conclusion: High levels are present in the blood of women with CMV. There is a decreased level of Cortisol in women miscarriage with CMV infection which is statically significant.